Seismic reliability analysis for strengthening of reinforced-concrete hospital building with base isolation Frames (Journal of Civil Engineering Researchers, 2022)
When an earthquake occurs in a region, it causes structural damages to buildings. Retrofitting these damaged structures before earthquakes to happen reduces the potential hazards and minimizes future casualties. In this paper, the seismic assessment of Reinforced Concrete (RC) structures inadequately to withstand seismic loads due to changing demands, and their retrofitting is studied. After a brief introduction of seismic retrofit described for existing structures, methods of assessing the seismic vulnerability of existing buildings are presented. To show the effect of the selected retrofit approach on the seismic behavior of RC buildings, an existing hospital building was selected as the case study. Since the use and occupancy of the selected RC building designed as a residential building had changed, a seismic assessment was carried out using Opensees software to show whether the building needs seismic retrofit or not. After macro modeling to assess the seismic behavior of the structure, the dynamic analysis was conducted by applying 7 earthquake records on soil type B based on Iranian seismic code. Selecting the retrofit approach, which contains using Lead Rubber Bearing (LRB), was performed based on Iranian codes. To consider the uncertainties related to the ground motion, 27 ground motion time histories were utilized and results showed that the building needs seismic retrofit because of the increasing demands. Furthermore, the performed reliability study illustrated an effective role in improving the seismic behavior of the buildings under earthquake loads by the retrofit method.
Keywords: Reliability analysis; Seismic Assessment; Retrofit; RC Structure; LRB; Monte Carlo Simulation